2014
DOI: 10.1590/s1516-8913201402505
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Gliclazide Loaded Microcapsules

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…The data indicate more linearity when plotted by the zero-order kinetic model. Hence, it can be concluded that the major mechanism of drug release follows zero-order kinetics [21].…”
Section: Resultsmentioning
confidence: 98%
“…The data indicate more linearity when plotted by the zero-order kinetic model. Hence, it can be concluded that the major mechanism of drug release follows zero-order kinetics [21].…”
Section: Resultsmentioning
confidence: 98%
“…All analysis was done in triplicate, then the average ± SD was calculated using Microsoft office, 2010. 14…”
Section: Evaluation Of the Entrapment Efficiency (Ee)mentioning
confidence: 99%
“…Gliclazide is a member of second-generation sulfonylureas ( Figure 1) and is primarily used as an oral hypoglycemic drug in NIDDM (non-insulin-dependent diabetes mellitus). İt produces an antidiabetic effect through selectively inhibiting pancreatic K + ATP channels [8].…”
Section: Introductionmentioning
confidence: 99%